Towards a land of memories, stories and tragedies: The image of Peru in the Anglophone press in China (1874-1939) - Lizarme Villcas, Nashely (2024)
The article analyzes the representation of Peru in the English-speaking press in China between 1871 and 1939. During this period, China was interested in learning about Latin America and Peruvian’s economic, political, and social situation, particularly the living and working conditions of Chinese immigrants in Peru. While much of the research regarding the Chinese presence in Peru has focused on how Peruvians perceived Chinese immigrants, this work seeks to contribute to the analysis of the imaginary of Peru in China, particularly in the English-language media regularly published in Shanghai.